The vortex : a true story of history's deadliest storm, an unspeakable war, and liberation - Carney, Scott, 1978-; Miklian, Jason (Ecco, an imprint of HarperCollins Publishers, 2022)
This fast-paced, meticulously detailed book tells the story of the Great Bhola Cyclone, the deadliest storm in modern history, which killed 500,000 people in Pakistan, and its aftermath as told through the eyes of the men and women who witnessed it.